Analysis Of Internal Control System For Merchandise Investory At Ahass 6804 Quantum Penarik Motor - Riesti, Lorenza; Wagini, Wagini; Ariska, Yesi Indian (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2025)
The purpose of the study is to find out the internal control system for merchandise inverntory at Ahass 6804 Quantum Penarik Motor village Penarik, regency Teramang Jaya, district Mukomuko. The data collection method was carried out using interview, observation and documentation methods. The analytical methods used is Qualitative and Comparative analysis. The research results show that there is no conformity between Mulyadi’s theory (2016:488) and the conditions that occur in Ahass 6804 Quantum Penarik Motor shop for organizational elements, because according to Mulyadi’s theory the physical inventory count must be carried out by a special committee formed from werehouse employees. Meanwhile, what happened at the Ahass 6804 Quantum Penarik Motor shop was that the physical calculations were carried out directly by the werehouse department. For elements of the authorization system,recording procedures and employees, there is conformity and non-coformity between Mulyadi’s theory (2016:488) with the Ahass 6804 Quantum Penarik Motor shop, suitability is found in the list of physical inventory count results signed by the chairman of thr physical inventory count committee and the recording of the results of the physical inventory count based on a physical cound card whose veracity has been checked. There is a compatibility between Mulyady’s theory (2016:488) Ahass 6804 Quantum Penarik Motor shop puler for elements of healthy practice, because with Ahass 6804 Quantum Penarik Motor shop the physical calculation card for merchandise inventory has been numbered sequentially, inventory checking has been carried out twice by the inventory counting section and then by inventory checking.